The Effect of Digital Marketing Through Social Media and Tourism Attractiveness on Visitor Interest - Aliyah, Khotimatul; Kisworo, Bagus; Miraj, Safri; Gupta, Sachin (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2024)
Social media marketing and tourist attraction are among the factors that influence visiting interest. This study aims to analyze the effect of digital marketing through social media on visiting interest in Kandri Tourism Village, Gunungpati, Semarang. The research method used associative causal quantitative research. The sampling technique used was a non-probability purposive sampling technique, and a sample of 100 respondents was obtained. The data collection technique in this study was to distribute questionnaires directly. Data analysis using SPSS (Statistical Program for Social Science) v.26 for Windows software. The data validity test uses validity and reliability tests. The data analysis technique uses inferential data analysis techniques, namely multiple linear regression tests. The results showed that social media marketing and tourist attraction simultaneously positively affected visiting interest in Kandri Tourism Village, which amounted to 49.5%. This research provides references regarding factors influencing visiting interest for future research and for tourist village managers to utilize social media marketing to promote tourist villages more effectively. In addition, efforts to increase tourist attractiveness can also support increased visitor interest.